Prenatal diagnosis and outcome of lymphangiomas and its relationship with fetal chromosomal abnormalities. (1st February 2016) - Arisoy, Resul; Erdogdu, Emre; Kumru, Pinar; Demirci, Oya; Yuksel, Mehmet Aytac; Pekin, Oya; Tugrul, Semih; Aydin, Hatip
Abstract: Objectives : Our aim was to evaluate ultrasound findings and perinatal outcome after prenatal diagnosis of lymphangioma. Methods : This was a retrospective case series study. We searched the archives of our ultrasound database at our center for cases with the prenatal diagnosis of the lymphangioma in the period between January 2008 and November 2014. We described maternal, fetal and perinatal variables for all cases. Results : Nine fetuses with lymphangioma were identified. All cases were diagnosed during the second and third trimesters with the average gestational age of 22.6 ± 3.9 weeks. The average diameter of lymphangioma was 55.4 ± 20.1 mm at the time of diagnosis. Five fetuses (55.6%) had lymphangioma on the neck, and four fetuses (44.4%) had lymphangioma on other localizations. Normal fetal karyotype was detected in all cases. There were a total of six live births, one intrauterine death and two medical terminations of pregnancy following the diagnosis of lymphangioma. No abnormal Doppler finding or hydrops were detected in the antenatal follow-up of remaining six cases. Conclusion : The risk of chromosomal abnormalities is very low in pregnancies with isolated lymphangioma. The outcome of pregnancies with lymphangioma is generally favorable and prognosis depends on their locations and size.